The Influence of Operational Conditions on the Cold Test of CFB Boiler for Fluidization Process Using Air Cap Bell-Type - Mauk, Syifa Ainun; Pajri, Oppy Oktaviani; Ashfani, Khansa; Alwan, Hafid (Universitas Medan Area, 2025)
Fluidization is a method of contacting solid particles with a fluid so that they exhibit fluid-like properties. One industrial application of fluidization is the fluidization process in power plants using Circulating Fluidized Bed (CFB) boilers where air is blown from the bottom as coal is burned to keep it suspended above the furnace. The variations used were air flow rates of 32,09; 62,72; 91,89; 123,98 and 154,61 m3/hour, bed material heights of 20; 30 and 40 cm, and types of bed material of coal and silica sand. This research aims to investigate the effects of changes in primary air flow, bed height, and type of bed material in the bed on fluidization behavior in CFB using an air cap bell-type through cold testing for easier observation. The results of this research show that at an air flow rate of 154,61 m3/hour and a bed material height of 40 cm, the highest pressure drop was obtained. For silica sand and coal, the pressure drops were 3,51 and 1,11 kPa, respectively. For the silica sand bed material, various fluidization phenomena were observed, while for coal, only the fixed bed phenomenon was observed.